Characterization of Acute Poisoning in Hospitalized Children in Southwest China - Li, Zhu; Xiao, Li; Yang, Lin; Li, Shaojun; Tan, Liping (Frontiers in Pediatrics, 2021)
Objective: Acute poisoning in children is characterized by regional differences. This study described the basic situation of childhood poisoning in southwest China based on hospitalized cases. Data and Methods: A total of 1,076 acute poisoning cases among hospitalized children admitted to Children's Hospital of Chongqing Medical University from January 2012 to December 2020 were included in this study. Clinical data such as gender, age, living environment, poisonous substance, and cause of poisoning were statistically described. Trends of length of hospital stay, population distribution, poisonous substances, and causes of acute poisoning in the hospitalized children were compared over time. Results: The cohort comprised 588 males and 488 females; 811 cases lived in rural areas and the rest resided in urban areas. Most cases were between early childhood and school age. Poisoning usually occurred at home (973 cases, 90.4%). Pesticides (381 cases, 35.4%) and drugs (275 cases, 25.6%) were the two most common poisonous substances. Two main causes of poisoning were accidental taking (755 cases, 70.2%) and suicide (177 cases, 16.4%). The results of univariate analysis of suicide showed significant correlations among gender, place of residence, age, poisonous substance, and place of suicide (P < 0.001), while living environment (town), age (adolescence), and poisonous substance (pesticide, drug) were independent risk factors (P < 0.05). There was no significant change in the length of hospital stay for poisoning over time. The overall number of hospitalizations presented a decreasing trend, while the number of urban children gradually increased. The proportion of adolescent poisoned children and suicidal children increased in the last 3 years. Conclusion: Optimizing the package and distribution channels of pesticides and drugs, raising safety awareness of children to avoid accidental injuries, and paying attention to children's mental health are measures that are necessary to prevent poisoning in children.